Carbon dioxide narcosis due to human error in a dog. Issue 2 (24th June 2020) - Phillips, Victoria; Mathis, Alessandra
Abstract : Incorrect assembly of a parallel Lack (Mapleson A) breathing system resulted in carbon dioxide narcosis in a dog due to rebreathing of expiratory gases. A seven‐year‐old, male neutered Rottweiler, weighing 49 kg, failed to recover after discontinuation of inhalational anaesthesia following a forequarter amputation for osteosarcoma. During recovery, the endotracheal tube had been connected to a parallel Lack anaesthetic breathing system delivering 100 per cent oxygen at 5 l/minute. Although a prolonged recovery, 30 minutes, all vital parameters were considered within normal limits until a severe increase in respiratory effort was noted. Capnography revealed rebreathing with an end‐tidal carbon dioxide tension of >150 mm Hg (>19.9 kPa). The dog was transferred to a circle breathing system, and with normalisation of the capnogram, recovery proceeded without further complications. Visual inspection of the parallel Lack breathing system revealed misassembly which had resulted in rebreathing of expiratory gases, extreme hypercapnia causing prolonged recovery due to narcosis.